2021
DOI: 10.1136/bmjopen-2020-040109
|View full text |Cite
|
Sign up to set email alerts
|

Effective coverage of nutrition interventions across the continuum of care in Bangladesh: insights from nationwide cross-sectional household and health facility surveys

Abstract: IntroductionImproving the impact of nutrition interventions requires adequate measurement of both reach and quality of interventions, but limited evidence exists on advancing coverage measurement. We adjusted contact-based coverage estimates, taking into consideration the inputs required to deliver quality nutrition services, to calculate input-adjusted coverage of nutrition interventions across the continuum of care from pregnancy through early childhood in Bangladesh.MethodsWe used data from the 2014 Banglad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Poor EC of MNH visits identified in the current study are consistent with the studies conducted in Bangladesh [54], Cambodia [55], and other LMICs of South Asia and Sub Saharan Africa [18,46]. Studies conducted in Nepal reported poor quality of ANC [48] and had low uptake of recommended antenatal interventions (e.g., ANC counselling or iron or tetanus toxoid injections) [56].…”
Section: Ec Of Routine Mnh Visits and Determinantssupporting
confidence: 85%
“…Poor EC of MNH visits identified in the current study are consistent with the studies conducted in Bangladesh [54], Cambodia [55], and other LMICs of South Asia and Sub Saharan Africa [18,46]. Studies conducted in Nepal reported poor quality of ANC [48] and had low uptake of recommended antenatal interventions (e.g., ANC counselling or iron or tetanus toxoid injections) [56].…”
Section: Ec Of Routine Mnh Visits and Determinantssupporting
confidence: 85%
“…Overall 64 measures that met the eligibility criteria were reported across the 33 studies; 36 measures of interventions among women and newborns ( Table 3 ), 29 measures among children under five ( Table 4 ), and 0 measures for children ages five to nine. Seventeen studies explicitly defined the measures as effective coverage, three studies referred to measures as effective coverage but reported them according to the adjustments made: input-adjusted coverage [ 50 , 55 ] and structure-adjusted coverage and process-adjusted coverage [ 39 ]. The remaining studies did not use the term effective coverage, instead measures were defined as: adequate contact with high quality care [ 52 ], content coverage [ 36 ], coverage of obstetric services [ 32 ], facility readiness [ 48 ], high quality contacts [ 34 ], missed opportunities [ 37 ], population access to quality care [ 42 ], quality coverage [ 64 ], quality-adjusted contact [ 51 ], quality-adjusted coverage [ 40 ] and treatment pathway [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Where multiple interventions were being delivered within a single service such as childbirth, postnatal care and sick child care, studies either reported a combined measure or separate measures for each intervention delivered ( Table 3 and Table 4 ). For example, four studies of sick child care reported a single measure for a package of interventions for the management of childhood illness, including diagnosis and treatment of malaria, treatment of diarrhoea with oral rehydration solution and treatment of respiratory infections [ 33 , 38 , 39 , 50 , 55 ]. Conversely, two studies on sick child care presented a separate measure for each intervention examined [ 43 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge is ensuring the quality of nutrition interventions provided at ANC contacts, without which programmes will not fully harness the benefits of these interventions on maternal and child nutrition outcomes. Moreover, a recent study reported incomplete readiness of healthcare facilities to provide nutrition interventions during ANC (51%) [ 12 ]. Nutrition input-adjusted coverage was suboptimal (18% for ANC) and disproportionately affected the poor and women with lower educational attainment.…”
Section: Introductionmentioning
confidence: 99%